Indonesia's Economy since Independence - Thee, Kian Wie (Book collections on Project MUSE., 2012)
This book contains a collection of papers on various aspects of Indonesia's economic and its industrial development. It discusses the early independence period in the 1950s; the Soeharto era (1966-1998); and the ensuing two economic crises, namely the Asian Financial Crisis of 1997/98 and the Global Financial Crisis of 2008.